Recent developments in the research on biomarkers of cholangiocarcinoma in primary sclerosing cholangitis - Wannhoff, Andreas; Gotthardt, Daniel (Clinics and research in hepatology and gastroenterology, 2019)
Primary sclerosing cholangitis (PSC) is characterized by a chronic inflammatory process of the bile ducts of unclear aetiology. It is often complicated by cholangiocarcinoma (CCA) with a dismal prognosis. Early detection of CCA is important because treatment options for advanced disease are limited. Besides the established markers, like CA19-9, recent developments have been made using latest technologies. This review summarizes the recent advances and remaining limitations of biomarkers of CCA in PSC.
Available online 25 September 2018
Gesehen am 24.06.2019